2011
DOI: 10.3892/etm.2011.402
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interleukin-8 (IL-8) and IL-8 receptors on the migration of human keratinocytes, the role of PLC-γ and potential clinical implications

Abstract: Abstract. Interleukin (IL)-8 is a pro-inflammatory cytokine that has a direct effect on immune cells, including polymorphonuclear cells. Keratinocytes are a rich source of IL-8. However, there is little knowledge on the role of IL-8 in clinical wound healing and the direct biological effect of IL-8 on keratinocytes. In this study, the effect of recombinant human IL-8 (rhIL-8) on migration and adhesion was tested using HaCaT keratinocytes as a cell model. The cell functions were evaluated using impedance cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 29 publications
1
90
0
3
Order By: Relevance
“…Chemokines under investigation for the treatment of chronic wound are CCL2, CXCL8, and CXCL12. [43][44][45] Because of the multifaceted function of CXCL12, that includes its ability to promote angiogenesis and reepithelialization, recruit EPC, and reduces tissue scarring, it is a potential target for the treatment of dermal wounds. 43,[46][47][48] It has been shown that direct application or lentiviral induction of CXCL12 enhances wound healing in diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines under investigation for the treatment of chronic wound are CCL2, CXCL8, and CXCL12. [43][44][45] Because of the multifaceted function of CXCL12, that includes its ability to promote angiogenesis and reepithelialization, recruit EPC, and reduces tissue scarring, it is a potential target for the treatment of dermal wounds. 43,[46][47][48] It has been shown that direct application or lentiviral induction of CXCL12 enhances wound healing in diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 also plays a role in and is a marker of tumor progression and metastatic disease for a wide range of cancers including gliomas as well as breast and prostate cancers (23)(24)(25). Finally, IL-8 is prominent in keratinocytes after IHC staining; this presence suggests that it is a cell migration and chemotactic factor for keratinocytes, suggesting that IL-8 plays a role in wound healing (26,27). The effect of minimally invasive colon resection (MICR) on postoperative (postop) plasma IL-8 levels is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…which are associated with epithelialization [44]. IL8 has a profound effect on the migration of keratinocytes which is again critical to wound epithelialization [45]. In vitro experiments on the effect of recombinant human IL8 on keratinocyte proliferation revealed a rise in cell numbers, whereas in vivo topically applied IL8 on human skin grafts in a chimeric mouse model enhanced re-epithelialization due to elevated numbers of mitotic keratinocytes [46].…”
Section: Resultsmentioning
confidence: 99%